Trends in Craniofacial Fellowship Career Outcomes: A Call for Expanding Professional Opportunities in Craniofacial Surgery. Issue 1 (21st January 2023) - Rogers, Ashley E.; Sayyed, Adaah A.; Marable, Julian; Harshbarger, Raymond; Taub, Peter J.; Taylor, Jesse; Baker, Stephen B.
Abstract : Purpose: Limited available pediatric plastic surgery positions fail to accommodate the increasing number of craniofacial fellows trained annually. However, many adult indications have increased the demand for craniofacial expertise. Given new opportunities available to craniofacial surgeons, the authors aim to evaluate career prospects for recent craniofacial graduates and explore additional career opportunities. Methods: Upon approval from the American Society of Craniofacial Surgeons (ASCFS), an anonymous online survey invitation was sent to craniofacial fellows who graduated from 2016 to 2021. Respondents were queried regarding their craniofacial fellowship and subsequent career prospects. Results: A total of 124 eligible participants were identified, of which 30 (24.2%) responded. Craniomaxillofacial case distribution at respondents' current practices varied, with 42.3% reporting a 50% to 75% craniofacial caseload and 38.5% reporting less than 25%. Craniofacial trauma reconstruction was performed most at current positions (92.3%), followed by general reconstruction (92.3%) and breast surgery (69.2%); the least commonly performed was facial feminization (23.1%). Most respondents desired an increased craniomaxillofacial caseload (65.4%). However, 26.9% were unable to secure their current position before fellowship completion, and 80.0% cited limited craniofacial job availability. Recommendations to improve fellowship comprehensiveness and increase candidate competitiveness included increased facial feminization, facial esthetic, and microsurgical experience. Conclusion: To adapt to trends in craniomaxillofacial surgery, ASCFS should encourage developing fellowships that increase exposure to gender-affirming, adult craniofacial reconstruction, orthognathic, and skeletal facial esthetic surgery. Expanding training beyond congenital deformities can provide additional employment opportunities while maintaining excellence and innovation in facial plastic surgery.